WAYS OF PRACTICAL MANIFESTATION AND DISSEMINATION OF EXTREMIST AND TERRORIST MOVEMENTS ON THE INTERNET - Атажанов Ахтам Юсупович (Galaxy International Interdisciplinary Research Journal, 2023)
Youth as a socio-demographic group is an active communicant of the information field, but today the information field is becoming uncontrollable. Free access to the Internet makes young people potential victims of radical ideologies, extremism and terrorism. The article presents the ways of practical manifestation and dissemination of extremist and terrorist movements on the Internet.